2006
DOI: 10.1021/ja064177q
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Solution Route to Macroscopic Amounts of Hydrogen Terminated Silicon Nanoparticles

Abstract: A new solution route for preparing gram-scale, hydrogen terminated silicon nanoparticles is presented. Dimethoxyethane and diocytl ether have been used to prepare silicon nanoparticles via a solution reaction between sodium silicide and ammonium bromide. The reaction products are isolated as a clear yellow-orange solution and a dark black powder. Both the solution and the powder have been characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
129
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 18 publications
5
129
0
2
Order By: Relevance
“…From this plot, it can be seen that a number of materials fall close to the gravimetric and temperature ranges considered necessary for vehicular applications. Others, such as silicon nanoparticles [58][59][60][61] release hydrogen at too high a temperature, and do not release hydrogen with adequate gravimetric capacity. When the CHSCoE concluded its research, chemical regeneration of spent fuel from ammonia borane had been demonstrated in the laboratory with two major variants with over ten regeneration schemes having been partially or completely demonstrated, thereby showing potential to overcome regeneration as a barrier to the technological implementation of chemical hydrogen storage; however, more R&D is need to reduce cost and increase efficiencies.…”
Section: Hydrogen Storage Research In the Doe Chemical Hydrogen mentioning
confidence: 99%
“…From this plot, it can be seen that a number of materials fall close to the gravimetric and temperature ranges considered necessary for vehicular applications. Others, such as silicon nanoparticles [58][59][60][61] release hydrogen at too high a temperature, and do not release hydrogen with adequate gravimetric capacity. When the CHSCoE concluded its research, chemical regeneration of spent fuel from ammonia borane had been demonstrated in the laboratory with two major variants with over ten regeneration schemes having been partially or completely demonstrated, thereby showing potential to overcome regeneration as a barrier to the technological implementation of chemical hydrogen storage; however, more R&D is need to reduce cost and increase efficiencies.…”
Section: Hydrogen Storage Research In the Doe Chemical Hydrogen mentioning
confidence: 99%
“…The synthesis method involves reaction of the Zintl salt (NaSi) with ammonium bromide [26,27]. The formation reaction proceeds via a chemical "metathesis" process, in which hydride-covered elemental silicon are formed with several by-products, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a metal silicide promises large quantity synthesis of silicon nanoparticles even by a liquid phase solution process. For example, Kauzlarich and co-workers successfully produced more than a decamilligram of silicon nanoparticles by the following chemical reaction [33]: NaSi + NH 4 Br → Si/H + NaBr + NH 3 (1) Fig. 13.…”
Section: Synthesis Of Si Nanoparticlesmentioning
confidence: 99%